The impact of good corporate governance on corporate sustainability on LPD in Bali on risk management as mediation - Ida I Dewa Ayu Yayati Wilyadewi (Enrichment : Journal of Management, 2023)
Based on local knowledge, village credit institutions (LPD) are an essential part of making the village economy work and getting it moving. LPD management and low-risk mitigation have deteriorated LPD health. This study aims to identify good corporate governance for corporate sustainability in LPD in Bali with risk management as a mediation plan. Explanatory research with a quantitative approach is used. There are 100 LPDs included that are determined using proportional random sampling. The distribution of questionnaires and interviews was conducted with LPD leaders randomly. Data analysis was performed using SmartPLS 3.0. Ultimately, for corporate sustainability to be possible, the LPD component must improve good corporate governance by achieving positive and significant influence. Furthermore, risk management is directly influenced by good corporate governance, with significant positive results. Legalizing Pararem (local village rules) improves LPD risk management in Bali. The third result was a significant favorable influence between risk management and corporate sustainability. Indicators in risk management indirectly provide risk mitigation to improve LPD corporate sustainability. The impact of sound corporate governance on a company's capacity to maintain itself can be moderated by management. The impact of excellent corporate governance on LPD's corporate sustainability in Bali may be increased by implementing risk management, which comprises liquidity risk, credit risk, and operational risk management.